Unlocking Ride-Sharing's Potential in Birendranagar, Surkhet, Nepal - Prasad Dhungana, Dillu (Journal of Entrepreneurship & Management Studies, 2025)
This paper investigates the opportunities of ride-sharing in Birendranagar, a semi-urban city of Nepal, where transportation is a problem. A quantitative design was used whereby structured questionnaires were employed to collect data from 168 residents and stakeholders and analyzed with correlation and multiple regression. The study measures the effects of technology, education, and security on adoption of ride-sharing. Results indicate the presence of strong positive correlation of ride-sharing opportunities and technology as well as security, and education does not have any significant effect. The results of regression analysis reveal & security to be the most important predictor, and technology has a minor effect. According to the model, Beyond the data, other hidden variables continue to influence whether the technology will be adopted. Security, such as physical security, data security, and trust, which are the central focus of the study, plays a key role in the enhancement of ride-sharing in new urban locations, which can be applied practically in terms of policy formulation and service development.